من مواقف ابن باديس - زغينة, محمد (الحياة, 1999)
Keywords: Réformisme – Mzab

أعمالي في الثورة - بيوض, إبراهيم بن عمر (جمعية التراث, 1990)
Keywords: Réformisme – Mzab

الامام إبراهيم بيوض رائد الحركة الإصلاحية في الجنوب الجزائري 1339-1401هـ/1920-1981م - قرقب, عيسى (جامعة قسنطينة, 1996)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

الشيخ إبراهيم بيوض ومنهجه في الإصلاح (1899م-1981م) - سكحال, نور الدين (جامعة الامير عبد القادر للعلوم الإسلامية, 1995)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Institut al-Hayat 1925-1962 : Un exemple d'école réformiste ibadite au M'zab - Bendrissou, Salah (Université Paris 8, 1994)
Keywords: Réformisme – Mzab

Dawr al-Imām Bayyūḍ fī ‘l-Nahḍa al-Waṭaniyya al-Jazā’iriyya wa-Muqārana bi’l-ʿAllāma bin Bādīs - Qarqab, ʿĪsà (Revue d'Histoire Maghrébine, 1997)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Islam et pensée contemporaine en Algérie: la revue al-Asâla, 1971-1981 - Deheuvels, Luc-Willy (Centre national de la recherche scientifique, 1991)
Photocopy of pp. 69, 100-101 (Ibāḍīs).* Speaking of the presence of Islamic rites and schools in the journal, Deheuvels writes of the Ibāḍīs, who counted more than 100.000 persons in Algeria in the 1970s, that their participation in al-Aṣāla has been minimal; only the Faqīh and historian Sul. b. Dāwud b. Yūsuf (see Ibn Yūsuf) has been associated regularly with the journal.
Keywords: Réformisme – Mzab

Risāla ilà al-Shaykh Bayyūḍ ʿan Humūm al-Muslimīn - Fayṣal, Shukrī (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

De Ibadiyya hun geschiedenis en leer Ibrahim Bayyud : een 20 e eeuwse Ibadi-shaykh in beschouwing genomen - Aken, Jos Van (Universiteit Utrecht, 1994)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab